The Impact of Artificial Intelligence (AI) for Transforming Tourism Marketing on the USA Industry Practices - Abid, Raghib; Saha, Palash; Islam, Md. Mominul (Journal of Information System and Informatics, 2025)
This study explores the transformative role of Artificial Intelligence (AI) in tourism marketing, highlighting its ability to enhance personalization, operational efficiency, and consumer engagement. The objective is to bridge the gap between theoretical capabilities and practical applications of AI in the USA tourism marketing. The methodology employs a PRISMA-based approach, focusing on recent studies from 2020 onward to analyze AI’s impact on marketing practices. A thorough examination of 389 publications obtained from databases like Scopus, Google Scholar, and Scimago for detailed qualitative analysis. The key contribution of this paper lies in its structural approach, which discuss the potential of various AI tools such as tailored recommendations and AI chatbots etc., offering fresh insights on their influence on the American Tourism Marketing sector. The report presents a framework for assessing the impact of AI on customer satisfaction and productivity, providing pragmatic solutions for tourism enterprises. In near future AI will develop enhancing human critical thinking and converting human cognition capabilities.